2016
DOI: 10.1371/journal.pone.0162916
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Increases CD133 Positive Cells that Show Low Sensitivity to Cytostatics in Neuroblastoma

Abstract: Valproic acid (VPA) is a well-known antiepileptic drug that exhibits antitumor activities through its action as a histone deacetylase inhibitor. CD133 is considered to be a cancer stem cell marker in several tumors including neuroblastoma. CD133 transcription is strictly regulated by epigenetic modifications. We evaluated the epigenetic effects of treatment with 1mM VPA and its influence on the expression of CD133 in four human neuroblastoma cell lines. Chemoresistance and cell cycle of CD133+ and CD133− popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…This increase, found in the CD133+ cells was not caused by elimination of CD133− cells. Moreover, VPA treatment enhanced clonogenicity and the ability to generate neurospheres, increased Akt phosphorylation and induced expression of the pluripotency transcription factors (Oct-4 (octamer-binding transcription factor 4), Nanog (Homeobox Transcription Factor Nanog), Sox2 (sex determining region Y)) [ 133 ]. Similar increase of CD 133+ cells was found also in glioblastoma cells treated by VPA [ 134 ].…”
Section: Mechanisms Of Hdac Inhibitors Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase, found in the CD133+ cells was not caused by elimination of CD133− cells. Moreover, VPA treatment enhanced clonogenicity and the ability to generate neurospheres, increased Akt phosphorylation and induced expression of the pluripotency transcription factors (Oct-4 (octamer-binding transcription factor 4), Nanog (Homeobox Transcription Factor Nanog), Sox2 (sex determining region Y)) [ 133 ]. Similar increase of CD 133+ cells was found also in glioblastoma cells treated by VPA [ 134 ].…”
Section: Mechanisms Of Hdac Inhibitors Actionmentioning
confidence: 99%
“…Decitabine and VPA both induced apoptosis and the combination increased their effects both in vitro and in vivo on leukemic cells and on medulloblastoma and rhabdomyosarcoma that develop in Ptch1 (Protein patched homolog 1) knockout mice [ 143 , 144 ]. On the contrary, this combination induced the CD133 expression in neuroblastoma cells with the methylated CD133 promotor [ 133 ]. Co-treatment of several cancer cells (prostate, pancreatic, lung and AML) with TSA and decitabine synergistically induced apoptosis [ 52 , 55 , 145 , 146 ].…”
Section: Combination Of Hdac Inhibitors With Other Anticancer Thermentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, studies have indicated the criticality of CD133-expressing Side populations in NB progression and therapy response. For instance, studies demonstrated that (1) non-adherent clumps of tumor cells that express CD133, OCT4, pAKT could grow in a serum-free medium with higher colony and neurosphere formation [98] ; (2) CD133 levels were directly associated with NB advanced disease stages and inversely correlated with postoperative survival time [95] ; and (3) CD133 + NB cells were more resistant to cisplatin, carboplatin, DOX, and etoposide (vs. CD133cells) and presented with increased phosphorylation of extracellular signal-regulated kinases (ERK) and P38 mitogen-activated protein kinases (P38) [99] . Consistently, an independent study showed that targeted inhibition of CD133 in NB cells produced increased RET expression and NB differentiation and, this response is mediated through the regulation of the p38 MAPK and phosphoinositide-3-kinase (PI3K)/ AKT pathways [97] .…”
Section: Cd133mentioning
confidence: 99%
“…Knocking down of the CD133 in NB cells effectively resulted in cell growth retardation [20]. Up-regulated CD133 decreased sensitivity to cytostatics in clinic [21]. Whether CD133 + cells have effects on responses towards chemotherapy and average survival time need to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%